Entrepreneurial learning evolutions in startup hubs : a post-pandemic perspective for lean organizations - Capolupo, Nicola (Entrepreneurial behaviour series., 2023)
Younger, leaner, and more innovative organizations have thrived in recent years despite the disruptions caused by Covid-19. For startups, the current scenario depicts an encouraging framework: they have demonstrated a strong and innate ability to adapt, finding new solutions to cope with changing economic conditions. To better understand the post-pandemic world, author Nicola Capolupo examines the shifts in training programs for startups in business incubators (hubs) from an entrepreneurial and organizational learning perspective. To intercept current shifts in training processes, Entrepreneurial Learning Evolutions in Startup Hubs comprise those levers that have led lean structures to adopt a holistic view in delivering organizational empowerment processes to new startups and entrepreneurs. Capolupo provides an in-depth case study, conducted through interviews with an inland area incubator that runs certified and recognized incubation paths for different startups The analysis of entrepreneurial learning evolutions in startup hubs provides practical input to startup and incubator managers on the strategic drivers of change in training processes, investigating new trends of Entrepreneurial Learning in lean organizations.